Pregnant Human Myometrial 1-41 Cell Viability Test on Vitamin D Administration - Aziz, Muhammad Alamsyah; Krisnadi, Sofie Rifayani; Handono, Budi; Setiabudiawan, Budi (Althea Medical Journal, 2023)
Background: Preterm labor is one of the universal causes of perinatal mortality worldwide. One of the causes of preterm labor is uterine muscle integrity problems. Some mechanistic studies show insight into vitamin D activity’s possible role in the injured muscle. This study aimed to determine whether vitamin D can increase muscle cell viability.Methods: This experimental research used human smooth muscle uterine myometrium cell line pregnant human myometrial (PHM) 1-41. The cells were cultured for 24 hours in hypoxia condition, then incubated with several doses of vitamin D. The PHM1-41 cell viability was measured using spectrophotometry. Data analysis was conducted using IBM SPSS 24.0. A p-value <0.05 was considered statistically significant. Results: The result showed that the minimum level of muscle cell viability after vitamin D incubation was with 300 nM administration, and the maximum level was after 10nM (88.57%+4.48 and 96.21%+2.13 respectively).Conclusions: Vitamin D at a specific dose can improve cell availability. The optimal dose to improve cell viability is 10 nM.